The involvement of limbic structures in typical and atypical absence epilepsy - ONAT, FİLİZ (ELSEVIER SCIENCE BV, 2013)
Typical and atypical seizures of absence epilepsy are thought to be generated by a rhythmogenic interplay between the cortex and the thalamus. However, the question remains as to which other subcortical and extrathalamic structures are involved in the pathophysiology of typical and atypical absence epilepsy. Limbic structures are not thought to be involved in typical absence seizures, since in animal models and human patients there is no evidence for the occurrence of spike-and-wave discharges of absence seizures in the limbic regions. However, there are a number of observations from animal models of absence epilepsy that point to a possibly important link between absence seizure mechanisms and limbic structures. Atypical absence seizures are distinct in many ways from typical absence seizures although they bear considerable clinical, EEG, and pharmacological resemblance to typical absence seizures. The differences between typical and atypical seizures of absence epilepsy appear to be circuitry dependent. While both typical and atypical absence seizures involve the cortico-thalamo-cortical circuitry, they each engage different neuronal networks within that circuitry. This review examines the involvement of limbic structures in typical and atypical absence seizures, shows that limbic circuitry forms an integral component of the absence epilepsy network and concludes that further knowledge of this component is important for understanding the complex relationships involved in absence epilepsy. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Absence seizures; GAERS; WAG/ Rij; GBL; MAM-AY9944; Brain circuitry; SPIKE-WAVE DISCHARGES; MEDIAL PREFRONTAL CORTEX; LENNOX-GASTAUT-SYNDROME; THALAMIC RETICULAR NUCLEUS; MAL-LIKE SEIZURES; GENERALIZED NONCONVULSIVE EPILEPSY; CORTICALLY GENERATED SEIZURES; CEREBRAL GLUCOSE-UTILIZATION; TEMPORAL-LOBE EPILEPSY; WAG/RIJ RATS